BIMBINGAN DAN KONSELING KOMPREHENSIF : DARI PARADIGMA MENUJU AKSI - Bhakti, Caraka Putra (JURNAL FOKUS KONSELING, 2015)
AbstractÂ Guidance and counseling undergo development which is quite rapid.There has been a shift in the paradigm guidance from traditional approach leads on the approach of the development and comprehensive. In line for the implementation of the guidance and counseling comprehensive a string of has done research that the results show effective for implemented.Along with that some policies the government affirmed a notch evident during the implementation guidance and counseling comprehensive. Required the follow-up to that planned in a comprehensive manner so that this approach can diimplementasi effectively. The implementation guidance and counseling comprehensive should be supported by understanding whole about the concept of development for the school counselor at. Now some way to strengthen the competence of a counselor with various activities as the seminar, workshop and training on the application of the guidance and counseling comprehensive. In the effectiveness of the implementation of the guidance and counseling comprehensive one of them supported by collaboration with relevant parties. A growing awareness that in the development of the potential of students it takes effective cooperation from various parties.Â Keywords: Guidance, Counseling,Comprehensive